Counter College: Third World Students Reimagine Public Higher Education. Issue 4 (November 2015) - Ryan, Angela
Abstract : In 1969, the discipline of Ethnic Studies emerged and was implemented at a handful of colleges throughout the country, most notably at San Francisco State College where the first School of Ethnic Studies was established that year. The idea of devoting space within traditional educational institutions to the study of a particular race or ethnicity has existed since at least the 1920s when Carter G. Woodson proposed Negro History Week and encouraged the study of African American history. While Black Studies is thus the oldest of such fields within American education history, its establishment within higher education is tied to the establishment of the larger discipline of Ethnic Studies. Ethnic Studies encompasses the critical study of racial and ethnic histories and cultures and it incorporates a wide variety of methodologies. The course of the discipline throughout the past forty years has resulted in a variety of approaches to this study, thus generalizing about the field as it exists today is complicated. One thing that may be said about Ethnic Studies in its current iteration, however, is that it bears little resemblance to the proposals that ushered it into existence.